DISPARITAS DAN UPAYA MENINGKATKAN KESEJAHTERAAN PETANI - Dahiri Dahiri (Pusat Kajian Anggaran, 2022)
The agricultural sector is one of the important sectors in the national economy which is reflected in the gross domestic product. However, the disparity in the welfare of farmers is still large. Within the agricultural sector, the level of welfare of food crop farmers is the lowest compared to the welfare of other sub-sectors. This paper aims to analyze and identify disparities in farmer welfare and efforts to improve farmer welfare according to the legislation in the field of agriculture. The method used is quantitative with the Anova test and Duncan's Post Hoc Test and The data source used is secondary data BPS. The results showed that there was a disparity in the welfare of farmers with 7 (cluster) levels of disparity in the welfare of farmers. Increasing the welfare of farmers through increasing production is prioritized in the food crops sub-sector and in the lowest cluster. Efforts to increase the production of the food crop sub-sector are to maintain the existing planted area, increase the productivity of food crops, and maintain price stability.